2022
DOI: 10.1002/cptc.202200009
|View full text |Cite
|
Sign up to set email alerts
|

Phenoxazine‐Sensitized CO2‐to‐CO Reduction with an Iron Porphyrin Catalyst: A Redox Properties‐Catalytic Performance Study

Abstract: We have evaluated six phenoxazine derivatives as visible light photosensitizers for the photochemical reduction of CO2 to CO with an iron porphyrin catalyst in organic media. The phenoxazine core was functionalized with electron‐donating or ‐withdrawing groups to modify the photophysical properties. Both singlet and triplet excited state potentials of the sensitizers spanned several hundred mV range and the ground state oxidation potentials spanned 250 mV. We observed that no correlation can be established bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…The same group in a recent report evaluated six phenoxazine derivatives as visible light photosensitizers for the photo-initiated CO 2 to CO reduction, using Fe-p-TMA as catalyst in CH 3 CN solution. 194 The photcatalytic studies demonstrated that the production of CO is strongly related to the oxidation potential of the Phen sensitizer. This unexpected result indicates that photosensitizer regeneration by the SED is the rate-limiting step of this catalytic system.…”
Section: Homogeneous Systemsmentioning
confidence: 99%
“…The same group in a recent report evaluated six phenoxazine derivatives as visible light photosensitizers for the photo-initiated CO 2 to CO reduction, using Fe-p-TMA as catalyst in CH 3 CN solution. 194 The photcatalytic studies demonstrated that the production of CO is strongly related to the oxidation potential of the Phen sensitizer. This unexpected result indicates that photosensitizer regeneration by the SED is the rate-limiting step of this catalytic system.…”
Section: Homogeneous Systemsmentioning
confidence: 99%
“…In such a CO 2 reduction system, the catalyst is reduced after gaining electrons from the oxidative/reductive quenching process of the excited photosensitizer to generate the catalytically active species. Apart from the noble metal complexes (i.e., Re, Ru, Rh, and Ir complexes ), many non-noble transition metal complexes, such as Mn, Fe, Co, Ni, and Cu complexes, have also been used in photochemical CO 2 reduction. Modifying the ligands from neutral to charged groups can stabilize the critical M–CO 2 and M–CO intermediates through noncovalent electrostatic interactions, thus promoting the CO 2 RR toward target products.…”
Section: Introductionmentioning
confidence: 99%
“…[12b,17] We found that neither PhCF 3 1 a nor B 2 pin 2 /KOH showed significant quenching toward the excited state *PC-I, consistent with their redox potentials. [18] While the mixtures of 1 a/B 2 pin 2 (1 : 1) and 1 a/B 2 pin 2 /KOH (1 : 1 : 1) exhibited more significant quenching to *PC-I (K sv = 28.0 for the former and K sv = 58.0 for the latter) (see ESI for more 19 F NMR and UV/Vis Absorption Spectroscopic Studies). These results suggested that B 2 pin 2 /KOH could facilitate the challenging SET reduction of PhCF 3 and subsequent fluoride elimination process.…”
Section: Methodsmentioning
confidence: 99%